학교급식 친환경쌀의 구매 결정 요인 분석 : 고성 생명환경쌀 사례를 중심으로 - 신영식 (한국농촌경제연구원, 2013)
This study analyses the factors that affect the purchase of environmentally-friendly rice for school meals, especially focusing on Goseong's Life Environment Rice. To obtain the data, 50 primary, middle and high schools in Gyeongsangnam-do were chosen for survey. A cross frequency analysis is conducted to identify the key explanatory variables that decide the purchase of environmentally-friendly rice for school meals. Also, a logit model is used to find a model that fits the survey data and to calculate marginal effects of several key variables. The study finds that key factors that affect the purchase of environmentally-friendly rice for school meals are the GAP mark, geographical environment, grade, and marketing channel. This study can be used for Goseong-gun to set up a plan to increase the demand for Goseong's Life Environment Rice.